Public-Private Participation in Energy Infrastructure in Middle East and North African Countries: The Role of Institutions for Renewable Energy Sources Diffusion - Somma, Ernesto; Rubino, Alessandro (International Journal of Energy Economics and Policy, 2016)
Investment in infrastructure, although historically dominated by public intervention, are experiencing a growing role for public and private partnership. This trend traced a steady increase since the start of privatization and liberalization process that took place in most OECD countries in the 90s and peaked in 2012. Middle East and North African (MENA) countries are hungry for infrastructural investment, but looking at the consolidated global trends in energy investment, it emerges that its performance is particularly poor in attracting private participation. However, Morocco was able to figure among the top destination countries for energy investment. Together with Jordan they represent the only two countries able to attract energy investment in the region mostly in renewable energy technology. Evidence shows that Morocco and Jordan are those that perform better in terms of political stability score and rule of law score according to the World Bank. The institutional and political endowment in MENA countries appear to be inappropriate to secure the level of infrastructural investment in the energy sector, in particular when dominated by long lead times and irreversibility. In this context, renewable energy sources investment offer a valid alternative, when the necessary pre-conditions are put in place and when the regulatory design is able to offset, at least partially, the higher country risk that investor are likely to face. Keywords: Public Private Partnership, Investment, Middle East and North Africa, Energy Transition, Institutional Endowment, Renewable Energy Sources Investment JEL Classifications: D02, L43, O13